Dissociable meta‐analytic brain networks contribute to coordinated emotional processing. Issue 6 (26th February 2018) - Riedel, Michael C.; Yanes, Julio A.; Ray, Kimberly L.; Eickhoff, Simon B.; Fox, Peter T.; Sutherland, Matthew T.; Laird, Angela R.
Abstract: Meta‐analytic techniques for mining the neuroimaging literature continue to exert an impact on our conceptualization of functional brain networks contributing to human emotion and cognition. Traditional theories regarding the neurobiological substrates contributing to affective processing are shifting from regional‐ towards more network‐based heuristic frameworks. To elucidate differential brain network involvement linked to distinct aspects of emotion processing, we applied an emergent meta‐analytic clustering approach to the extensive body of affective neuroimaging results archived in the BrainMap database. Specifically, we performed hierarchical clustering on the modeled activation maps from 1, 747 experiments in the affective processing domain, resulting in five meta‐analytic groupings of experiments demonstrating whole‐brain recruitment. Behavioral inference analyses conducted for each of these groupings suggested dissociable networks supporting: (1) visual perception within primary and associative visual cortices, (2) auditory perception within primary auditory cortices, (3) attention to emotionally salient information within insular, anterior cingulate, and subcortical regions, (4) appraisal and prediction of emotional events within medial prefrontal and posterior cingulate cortices, and (5) induction of emotional responses within amygdala and fusiform gyri. These meta‐analytic outcomes are consistent with a contemporary psychological model of affective processing in which emotionally salient information from perceived stimuli are integrated with previous experiences to engender a subjective affective response. This study highlights the utility of using emergent meta‐analytic methods to inform and extend psychological theories and suggests that emotions are manifest as the eventual consequence of interactions between large‐scale brain networks.